2016
DOI: 10.1007/s00535-016-1187-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and molecular analysis of hepatitis B virus reactivation in hepatitis B surface antigen-negative patients during or after immunosuppressive or cytotoxic chemotherapy

Abstract: Reactivation risk factors included male sex, advanced age, and hematological malignancy. HBV S gene immune-escape mutants were frequently found in the HBsAg-negative reactivation patients during or after immunosuppressive or cytotoxic chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…2 Immune system hypofunction and the use of immunosuppressive agents can lead to OBI reactivation and recurrence of typical serological evidence of infection. 3,4 The persistence of HBV DNA in the livers of individuals with OBI may provoke a mild but continuing necroinflammation, contributing to the progression of liver disease and increasing the risk of tumorigenesis. [5][6][7] The incidence of OBI was influenced by HBVendemic areas, the particular population studied, the public health status of the area, and screening methodology; and incidence differed extensively from previously reported values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Immune system hypofunction and the use of immunosuppressive agents can lead to OBI reactivation and recurrence of typical serological evidence of infection. 3,4 The persistence of HBV DNA in the livers of individuals with OBI may provoke a mild but continuing necroinflammation, contributing to the progression of liver disease and increasing the risk of tumorigenesis. [5][6][7] The incidence of OBI was influenced by HBVendemic areas, the particular population studied, the public health status of the area, and screening methodology; and incidence differed extensively from previously reported values.…”
Section: Discussionmentioning
confidence: 99%
“…OBI can be transmitted through blood transfusion, parturition, liver transplantation, and even through close contact . Immune system hypofunction and the use of immunosuppressive agents can lead to OBI reactivation and recurrence of typical serological evidence of infection . The persistence of HBV DNA in the livers of individuals with OBI may provoke a mild but continuing necroinflammation, contributing to the progression of liver disease and increasing the risk of tumorigenesis …”
mentioning
confidence: 99%
“…The virologic factors associated with increased risk of reactivation include high baseline HBV DNA, HBeAg positivity, and chronic hepatitis B 13–15 . HBV genotype has been increasingly linked to treatment response, disease severity and progression 16, 17 While its association with HBV reactivation is unknown, a few small studies have suggested infection with non-A genotype may be more prone to reactivation 17–19 . The prevalence of HBV genotypes has a variable and divergent worldwide distribution.…”
Section: Risk Factors Of Hbv Reactivationmentioning
confidence: 99%
“…In addition to rituximab use, other potential factors, including advanced age and male sex, have been reported to be associated with HBV-R (3,7,8). Recently, a relationship between antibodies to hepatitis B surface antigen (anti-HBs) and HBV-R was reported.…”
Section: Introductionmentioning
confidence: 99%